Reclassification of Urban Growth in Rural Area, Temanggung Regency, Indonesia - Holi Bina Wijaya; Imam Buchori (Department of Urban and Regional Planning, Diponegoro University, 2022)
Reclassification is part of urban growth together with the natural growth of birth and death, and migration from rural to urban areas. However, the reclassification has a deficiency in studies due to the urban growth discourses have much focused on the central force of existing urbanized areas. Historical data shows that the economic growth in urban areas is more due to a residual increase from migration growth and reclassification rather than natural growth. This paper contributes to the empirical context of the phenomenon of reclassification of urban growth and its following spatial changes in the rural area of Temanggung regency, Indonesia. The study utilizes the comparison analysis by examining the growth of industrial employment as an urban activity in rural areas, as well as looking at this relationship with changes in the physical built-up area as an indication of the urbanization process. This study found that the reclassification in Temanggung regency has encouraged urbanization in rural areas, through the development of industrial activities based on local resources and labor and promoted economic growth in rural areas. The reclassification that occurs is mostly due to the wood products manufacturing business that has been supported by the potential resources, and local workforce, rather than the active role of the government institution.